MEMAKSIMALKAN CITRA PERUSAHAAN MELALUI IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY - Budi Siregar (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2016)
Image or reputation of a feeling or a belief held by a person against an organization. In other words, a company's reputation is the evaluation (respect, appreciation and assessment) on the image of the organization of society. Corporate identity are symbols (such as logos and color schemes) used by organizations to identify with the community. Corporate image is the overall impression (feelings and beliefs) to an entity (organization, country or a particular brand) that exist in the public mind. Corporate social responsibility activities can form the image of the company if based upon a sincere motive for the consumer, but this becomes ineffective when the sincere motives become ambiguous and can actually worsen the company's image. One of the factors that influence whether or not a genuine assessment of corporate social responsibility actions are the benefits and the cause of corporate social responsibility activities are carried out. Therefore, activity is selected in the implementation of corporate social responsibility activities should be more responsive and appropriate to the conditions of the people and the environment in which the company or organization is operating.